2013
DOI: 10.1128/iai.00875-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Porphyromonas gingivalis Client Proteins That Bind to Streptococcus oralis Glyceraldehyde-3-Phosphate Dehydrogenase

Abstract: bCoaggregation of Porphyromonas gingivalis and oral streptococci is thought to play an important role in P. gingivalis colonization. Previously, we reported that P. gingivalis major fimbriae interacted with Streptococcus oralis glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and that amino acid residues 166 to 183 of GAPDH exhibited strong binding activity toward P. gingivalis fimbriae (H. Nagata, M. Iwasaki, K. Maeda, M. Kuboniwa, E. Hashino, M. Toe, N. Minamino, H. Kuwahara, and S. Shizukuishi, Infect. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
1
25
0
1
Order By: Relevance
“…GAPDH expression was altered in mutants with biofilm deficiencies for Streptococcus suis and Streptococcus mutans (40,41). In Streptococcus oralis, cell surface GAPDH acts as the binding site for biofilm formation by the periodontopathic bacterium Porphyromonas gingivalis (42,43). These studies indicated that GAPDH has a role in bacterial biofilms.…”
Section: Discussionmentioning
confidence: 72%
“…GAPDH expression was altered in mutants with biofilm deficiencies for Streptococcus suis and Streptococcus mutans (40,41). In Streptococcus oralis, cell surface GAPDH acts as the binding site for biofilm formation by the periodontopathic bacterium Porphyromonas gingivalis (42,43). These studies indicated that GAPDH has a role in bacterial biofilms.…”
Section: Discussionmentioning
confidence: 72%
“…Fructose-1,6-bisphosphate aldolase (Fba; PG1755) is an indispensable enzyme in glycolysis, gluconeogenesis, and the TCA cycle (29,30) as well as in both anabolic and catabolic amino acid processes (31). Glyceraldehyde-3-phosphate dehydrogenase (GapA; PG2124), involved in the glycolytic pathway, is responsible for the phosphorylation of glyceraldehyde-3-phosphate (29,32). The last three metabolic enzymes upregulated included 2-oxoglutarate oxidoreductase, subunit gamma (PG1809), acetyl coenzyme A (acetyl-CoA) synthetase (PGN_1117), and 2-ketoisovalerate ferredoxin oxidoreductase (PG1812).…”
Section: Resultsmentioning
confidence: 99%
“…P. gingivalis fimbriae are associated with biofilm formation [37] and binding to other bacteria [38]. Production of fimbriae is regulated by the FimS-FimR TCS encoded by PGN_0904-PGN_0903 in strain ATCC 33277, and PG 1432-PG1431 in strain W83.…”
Section: P Gingivalis Fimsr Tcsmentioning
confidence: 99%